Measuring systemic risk-adjusted liquidity (SRL)—A model approach - Jobst, Andreas A. (Journal of banking & finance, 2014)
Little progress has been made so far in addressing—in a comprehensive way—the negative externalities caused by excessive maturity transformation and the implications for effective liquidity regulation of banks. The SRL model combines option pricing theory with market information and balance sheet data to generate probabilistic measure of systemic liquidity risk. It enhances price-based liquidity regulation by linking a bank’s maturity mismatch impacting the stability of its funding with those characteristics of other banks, subject to individual changes in risk profiles and common changes in market conditions impacting funding and market liquidity risk. This approach can then be used (i) to quantify an individual institution’s time-varying contribution to expected losses from system-wide liquidity shortfalls and (ii) to price insurance premia that provide incentives for banks to internalize the social cost of their individual funding decisions.